Scope and forms of controlling teleworkers - Walentek, Dorota (Zakres i formy kontrolowania telepracowników, 2021)
Controlling teleworkers is a complicated process, mainly due to the lack of direct contact between the manager and subordinate. The purpose of the article was to identify the most common forms of controlling teleworkers by their supervisors. In order to achieve the goal, a literature review was carried out within the given scope and a quantitative survey was conducted using an online questionnaire among a group of several hundred teleworkers from various industries. The survey showed that the main reason of the control of teleworkers by their supervisors includes verifying the results of their work. Usually the tele-employer evaluates the results of a subordinate’s work in person or asks them to report on the results. The use of working time is generally verified by checking the teleworker’s reports and the time spent logged into the system; these forms of control were considered by teleworkers to be the most motivating for the desired employee behaviour.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 2 (60), s. 56-68
Keywords: teleworker; telecommuter; telework; telecommuting; teleworker control; forms of teleworker control; telepracownik; telepraca; kontrolowanie telepracowników; formy kontroli telepracowników